Visualization of the Spiral Ganglion Neuron in Vivo Using a Novel 177Lu Nuclear Molecule Label - Chenyang Kong; Xiaohui Wang; Jintao Yu; Li Wen; Chengwen Zheng; Ge Yin; Kai Xu; Weiwei He; Hao Wang; Xiaoli Lan; Dawei Jiang; Yu Sun (Advanced Science)
Abstract For patients with severe and profound hearing loss, cochlear implant (CI), a common and effective modality for restoring hearing, directly stimulates spiral ganglion neurons (SGNs) to generate electrical activity and form auditory perception. However, the postoperative outcome of CI is significantly influenced by the number of surviving SGNs, ​​which is a key focus of preoperative evaluation​​. Existing audiologic function and radiographic tests cannot directly demonstrate the integrity of inner ear primary neurons. In this study, ​​we developed and validated​​ a radionuclide‐labeled anti‐vesicular glutamate transporter 1 (anti‐VGLUT1) antibody‐drug and achieved animal‐level in vivo imaging of cochlear SGNs using nuclear imaging. By screening the public single‐cell sequencing database, it is found that VGLUT1 can serve as a representative cell membrane marker for SGN in the cochlea. The potential of anti‐VGLUT1 conjugated to the long half‐life 177Lu as a molecular probe to detect the relative number of SGNs in SGN‐injured mouse and pig models is explored. The study provides a novel method for assessing cochlear nerve integrity in vivo by visualizing target antigen expression levels through nuclear imaging. This approach is promising to help CI candidates with preoperative inner ear SGN integrity assessment, contributing to clinical decision‐making.